Urinary magnesium excretion and risk of cardiovascular disease in the general population - Michel Joosten; Ron Gansevoort; Kenneth Mukamal; Gerjan Navis; Johanna Geleijnse; Edith Feskens; Stephan Bakker (The Korean Society of Nephrology, 2012)
Magnesium has been favorable associated with many cardiovascular (CVD) risk factors. Previous studies on dietary magnesium and risk of CVD have yielded inconsistent results, possibly due to the use of dietary questionnaires or blood levels to assess magnesium exposure. Whether urinary excretion of magnesium, as reflection of actual dietary uptake, is associated with CVD risk remains unclear. We prospectively followed 7747 adults free of diagnosed cardiovascular diseases or cancer at baseline (1997-1998) from the community-based, observational PREVEND (Prevention of Renal and Vascular End-Stage Disease) Study. Urinary magnesium excretion was estimated from two 24-h urine collections and was measured by a xylidyl blue method on a Modular analyzer (Roche). During a median follow-up of 10.5 year, 638 CVD events occurred. After adjustment for age, BMI, sex, smoking status, alcohol consumption and educational attainment, urinary magnesium excretion showed a nonlinear relationship with CVD risk. The hazard ratios (HR) for CVD were significantly lower (P<0.05) among the highest four quintiles compared with the lowest sex-specific quintile (men: <2.56 mmol/24h; women: <2.09 mmol/24h). The lowest sex-specific quintile had an increased risk of CVD (HR, 1.53; 95% confidence interval (CI), 1.26-1.84) compared with the rest of the cohort after adjustment for confounders and urinary cations. Further adjustment for C-reactive protein, systolic blood pressure, total to HDL cholesterol ratio and type 2 diabetes, did not appreciably alter this association (HR, 1.44; 95% CI, 1.18-1.75). >In conclusion, low urinary magnesium excretion was associated with a higher risk of CVD, even after controlling for possible intermediates in the causal pathway such as blood pressure, diabetes and markers of inflammation and atherosclerosis. These results highlight the need to evaluate whether increasing the uptake of dietary magnesium could be effective for primary prevention of CVD.